1994
DOI: 10.2134/agronj1994.00021962008600060018x
|View full text |Cite
|
Sign up to set email alerts
|

Winter Wheat Yield and Grain Protein across Varied Landscape Positions

Abstract: Winter wheat (Triticum aestivum L.) yield varies greatly among landscape positions in the Palouse region of eastern Washington, yet N fertilizer is typically applied uniformly. Varying N fertilizer rates within fields to match site‐specific N requirements can increase fertilizer use efficiency; however, spatially variable N management programs are limited by their ability to predict site‐specific yield potentials and the resultant N requirements. The objective of this study was to ascertain the role of yield c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
59
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 12 publications
0
59
1
Order By: Relevance
“…While a portion of this variability was teased out by differences in year-to-year precipitation, other environmental, genetic, and management factors contribute to within-site variability, such as landscape elevation, slope, aspect (Mulla et al, 1992;Fiez et al, 1994;Yang et al, 1998), subsoil constraints , spring rainfall , crop rotation (Hammel, 1995), nutrient availability (Fiez et al, 1995), onset of drought and temperature stress (Gizaw et al, 2016), and crop genetics . Despite the heterogeneity of the landscape, iPNW growers still commonly apply single rates of fertilizer, particularly in the higher precipitation areas (Mahler et al, 2014).…”
Section: Opportunities For Site-specific N Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…While a portion of this variability was teased out by differences in year-to-year precipitation, other environmental, genetic, and management factors contribute to within-site variability, such as landscape elevation, slope, aspect (Mulla et al, 1992;Fiez et al, 1994;Yang et al, 1998), subsoil constraints , spring rainfall , crop rotation (Hammel, 1995), nutrient availability (Fiez et al, 1995), onset of drought and temperature stress (Gizaw et al, 2016), and crop genetics . Despite the heterogeneity of the landscape, iPNW growers still commonly apply single rates of fertilizer, particularly in the higher precipitation areas (Mahler et al, 2014).…”
Section: Opportunities For Site-specific N Managementmentioning
confidence: 99%
“…In addition to conserving soil water, the reduction or elimination of tillage is a strategy to combat water and wind erosion (Singh et al, 2012;Williams et al, 2014) in combination with continuous annual cropping (Thorne et al, 2003;Feng et al, 2011). Heterogeneous topography also challenges nutrient management due to significant variability in plant-soil-nutrient interactions and crop performance (Fiez et al, 1994(Fiez et al, , 1995 with opportunities for site specific N fertilizer management to mitigate differences in water and N use efficiencies across the landscape (Miao et al, 2011). A combination of these alternative cropping system strategies may increase productivity and economic returns (Tanaka et al, 2002;Alam et al, 2015;Babu et al, 2016), and multiple strategies may be needed (Kirkegaard and Hunt, 2010;Snapp et al, 2010).…”
mentioning
confidence: 99%
“…It is apparent that fertilizer use efficiency is a function of available water (Fiez et al 1994;Gutierrez-Boem and Thomas 1998). Thus, temporal variability in soil moisture (SM) clearly translates into temporal variability of crop response to N. It has been shown that crops response to N varies significantly from year to year, and that the magnitude of response is difficult to predict from 1 year to the next.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the body of literature on fertility management of hard wheat, relatively few studies have evaluated the effect of fertility practices on soft wheat yield and grain protein (Glenn et al 1985;Bole and Dubetz 1986;Bruckner and Morey 1988;Gravelle et al 1988;Carefoot et al 1989Carefoot et al , 1993Fiez et al 1994;Fowler 2003). These studies have demonstrated advantages to split applications of N in terms of improved crop yield and nitrogen use efficiency.…”
mentioning
confidence: 99%